2005
DOI: 10.1016/j.jsr.2005.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect on fatality risk of changing from secondary to primary seat belt enforcement

Abstract: Background: Most seat belt use laws originally passed in the United States contained language

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 11 publications
(12 reference statements)
0
17
0
Order By: Relevance
“…9,10,12,13 Primary laws, which allow an officer to stop and ticket occupants solely because they are unrestrained, have been shown to increase seatbelt use by as much as 22%, 10 and reduce fatality by as much as 7%. 12 Secondary laws, which permit a citation for lack of restraint use only if a motorist has been stopped for another reason, have been shown to increase seatbelt use as much as 11%. 10 One NHTSA study showed that primary laws increase seatbelt use on reservations.…”
Section: Introductionmentioning
confidence: 99%
“…9,10,12,13 Primary laws, which allow an officer to stop and ticket occupants solely because they are unrestrained, have been shown to increase seatbelt use by as much as 22%, 10 and reduce fatality by as much as 7%. 12 Secondary laws, which permit a citation for lack of restraint use only if a motorist has been stopped for another reason, have been shown to increase seatbelt use as much as 11%. 10 One NHTSA study showed that primary laws increase seatbelt use on reservations.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol consumption tends to be correlated with drinking-and-driving, which contributes to higher motor vehicle fatality rates (Asch & Levy, 1987;Legge & Park, 1994). Conversely, the unemployment rate and population density are negatively correlated with motor vehicle fatalities (Houston et al, 1995(Houston et al, , 1996Farmer & Williams, 2005). Finally, some scholars have argued that individuals with higher incomes place a higher value on time so they drive faster, thereby increasing the number of crash fatalities (Peltzman, 1975;Zlatoper, 1984).…”
Section: Methodsmentioning
confidence: 99%
“…A single-state time series analysis found the monthly nonfatal injury rate dropped by 5 percent after California switched to primary enforcement, but the fatality rate did not change (Houston & Richardson, 2002). In contrast, Farmer and Williams (2005) conclude states that switched from secondary to primary enforcement experienced a 7 percent reduction in the driver fatality rate. They employ cross-sectional time series regression analysis to examine the experience of 9 states and D.C. that upgraded during the period [1989][1990][1991][1992][1993][1994][1995][1996][1997][1998][1999][2000][2001][2002][2003], and compare these states to 14 states that had secondary enforcement throughout this time period.…”
Section: The Effectiveness Of Seat Belt Lawsmentioning
confidence: 99%
“…The Center for Disease Control and Prevention's systematic review of 13 high-quality studies (Shults, Nichols, Dinh-Zarr, Sleet, & Elder, 2004) found that primary laws increase belt use by about 14 percentage points and reduce occupant fatalities by about 8% compared to secondary laws. In another study, Farmer and Williams (2005) found that passenger vehicle driver death rates dropped by 7% when States changed from secondary to primary enforcement. On average, States that pass primary seat belt laws can expect to increase seat belt use by eight percentage points.…”
Section: Effectivenessmentioning
confidence: 98%